Dispersal of sibling coalitions promotes helping among immigrants in a cooperatively breeding bird - Sharp, Stuart P; Simeoni, Michelle; Hatchwell, Ben J (Proceedings of the Royal Society. B, Biological sciences, 2008)
Kin selection is a major force in social evolution, but dispersal is often assumed to reduce its impact by diluting kinship. In most cooperatively breeding vertebrates, in which more than two individuals care for young, juveniles delay dispersal and become helpers in family groups. In long-tailed tits (Aegithalos caudatus), however, offspring disperse to breed and helpers are failed breeders that preferentially aid kin. Helping also occurs among immigrants, but their origins are unknown and cooperation in these cases is poorly understood. Here, we combine long-term demographic and genetic data from our study population to investigate immigration and helping in this species. We first used a novel application of parentage analysis to discriminate between immigrants and unknown philopatric recruits. We then cross-checked sibship reconstruction with pairwise relatedness estimates to show that immigrants disperse in sibling coalitions and helping among them is kin biased. These results indicate that dispersal need not preclude sociality, and dispersal of kin coalitions may help maintain kin-selected cooperation in the absence of delayed dispersal.